Creaming among Caseworkers: Effects of Client Competence and Client Motivation on Caseworkers' Willingness to Help. (15th October 2020) - Guul, Thorbjørn Sejr; Pedersen, Mogens Jin; Petersen, Niels Bjørn Grund
Abstract: Frontline employees cope with high workloads and limited resources by directing their work attention and efforts toward particular clients. Yet, the role of client attributes in frontline employees' efforts to help clients remains undertheorized and empirically understudied. Using a survey experimental vignette design (2 × 2 factorial) among 1, 595 Danish caseworkers, the authors of this article provide new knowledge on how two generic nondemographic client attributes—competence and motivation—shape frontline employees' willingness to help their clients. We found that both the competence and motivation of clients affect caseworkers' willingness to exert extra time and effort helping clients. Specifically, caseworkers are most willing to help a client appearing both competent and motivated. Moreover, our data suggests that client motivation is more important than client competence for caseworkers' willingness to help. We end the article with a discussion of policy implications and directions for future research.